ASUHAN KEPERAWATAN PADA NY. M DENGAN INTERVENSI TERAPI BRAND DAROFF TERHADAP NYERI AKUT PADA PASIEN VERTIGO DI RUMAH SAKIT ABDUL MANAP KOTA JAMBI - Sisi, Aisyah Tita Rahmayuly; nurhusna (Jurnal Keperawatan Universitas Jambi, 2023)
Vertigo can be classified as a form of balance disorder or orientation disorder in a room. Many systems or organs of the body are involved in regulating and maintaining the balance of our body. Objective: To provide Brand Daroff therapy nursing care for acute pain in vertigo patients at Abdul Manap Hospital, Jambi City. The analysis showed that there was a diagnosis of acute pain with the intervention of giving Brand Daroff Therapy for 3 days. It was found that after the Brand Daroff therapy was carried out, there was a decrease in the pain scale on the first day of intervention with a pain scale of 7 (severe pain category) after the fourth day of intervention with a pain scale of 4 (mild mild pain category).Brand Daroff therapy can reduce acute pain in vertigo patients